Opportunity for Tourism Professional Development in Indonesia - Menara Simanjuntak (Bina Nusantara University, 2013)
This study focused on opportunities related to the professional growth of tourism in Indonesia at this time and in the future. The proportion of workers in the tourism sector, including the fourth largest after agriculture, manufacturing and non-manufacturing, tends to grow very fast, because tourists visiting Indonesia will increase sharply in coming years. The purpose of this study is to provide advice to the government, tourism, and educational institutions in Indonesia's tourism industry together, and to support each other to improve the quality and quantity of human resources in tourism in the present and the future in Indonesia. Data and information gathered from various sources perform literature review and discussion of the need for professional projections based on existing data and information and resume discussions and depth interview with lecturer of tourism and a SWOT analysis as a qualitative analysis. This study gave recommendation that Indonesia needs to improve the quantity and quality of human resources in tourism to become the domain of educational institutions, ranging from tourism vocational high school, Academy, College, and Tourism Courses at the University. Therefore the government should seriously facilitate the tourism educational institutions to achieve quality accreditation as required.